A PCR method to detect mating types of Cochliobolus heterostrophus. Issue 3 (3rd July 2018) - Dai, Yu-Li; Gan, Lin; Ruan, Hong-Chun; Shi, Niu-Niu; Du, Yi-Xin; Chen, Fu-Ru; Yang, Xiu-Juan
Abstract: A rapid and sensitive polymerase chain reaction (PCR) method was established for detection of mating types of Cochliobolus heterostrophus, the causal agent of southern corn leaf blight (SCLB). Two pairs of mating type-specific primers (ChMAT01-1 for MAT1-1 and ChMAT02-1 for MAT1-2) were designed and tested on DNA extracted from pure cultures, conidial suspensions or naturally infected corn leaf samples with C. heterostrophus . The PCR-based method exhibited specificity in differentiating mating types of C. heterostrophus from the closely related species C. sativus, C. carbonum, C. lunata, C. eragrostidis and Cochliobolus sp., as well as 13 other fungal genera. Specifically, the method was capable of reliably detecting mating types of C. heterostrophus at 0.0001 ng DNA for MAT1-1 or 0.01 ng DNA for MAT1-2 from pure cultures or from 10 conidia or one lesion of C. heterostrophus on inoculated or infected corn leaf samples, even in the presence of as high as 20 ng corn genomic DNA. This PCR assay also successfully detected mating types of C. heterostrophus in naturally infected samples.